VERBA TINDAK TUTUR BAHASA SIMALUNGUN - Anita Purba (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2019)
Meaning the unit external linguistic pragmatics or also called a special meaning in the English speech act verbs Simalungun include Assertif, Representative, Directives, commissive, Expressive, Declarative or Declaration. Expressive speech acts within speech act verbs excitement statement, can also be used in the speech act speech act verbs commissive the Promise. Speech acts Asserti Representative in the speech act verbs. A statement of fact, can also be used in the speech act speech act verbs commissive in Sadness statement. Expressive speech acts within speech act verbs passions would be something, could also be used in the speech act speech act verbs Directives in the Application.